The battle of the labyrinth - RIORDAN, RICK; RICK RIORDAN (New York: Disney.Hyperion Books, 2008)
Percy and his friends (Annabeth, Grover, and Tyson) enter Daedalus$1 (Bs shifting labyrinth to stop Luke Castellan from leading a Titan army invasion into Camp Half-Blood.s
Keywords: It follows fourteen-year-old Percy Jackson and his friends; revolve around the importance of personal choices